Correlations between motor and anthropometric variables and the performance of young competitors in alpine skiing - Stojan Puhalj; Blaž Lešnik; Alexander Povhe; Robi Kelc; Črtomir Matejek (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2022)
In alpine skiing we encounter many factors that affect the competitor to a greater or lesser extent and must be overcome or exploited in various ways. Broadly speaking, the nature of the activity plays its role just like the equipment, the spectators, the coach, etc., but the most important role is played by the competitor himself. Optimal synthesis is required for successful participation of top competitors with regard to physical, psychological and social skills and characteristics. During the transformation process (training) we help the competitor with different methods and means to transform from the initial to the final state, which is basically conscious transformation of numerous skills and characteristics of the competitor with impact on their personality as well. In this study we wanted to establish the extent to which certain anthropometric and motor skill parameters are related to competitive performance of younger boys aged 12 to 13 years in the Rauch Cup in the season 2014/15. Based on the measurements of seven tests of motor skills (MSKOK10 - Ten jumps with both feet, TESJCAS - Squat jump, MS20NVZP - 20m sprint, TREAOPTO - Optojump - Squat jump, MT400 - 400m run, MROS - Equilibrium stability index, and SKI9 - Figures-of-eight around 9 pins) and one measurement of anthropometric dimension (ABMI - Body Mass Index), we used the Pearson correlation coefficient to determine the correlation between individual variables and the performance of a sample of 34 young competitors in alpine skiing. The correlation of the whole set of variables regarding performance was determined using regression analysis. We have established a statistically significant correlation between the number of achieved points and variables MSKOK10, MS20NVZP, MT400 and SKI9 at the risk level of 1%. In the cases of TREAOPTO, MROSI and TESJCAS the correlation coefficients did not show statistically significant correlation. For the set of motor and anthropometric variables we have established a high and statistically significant linear correlation to the criteria (R=0.76, p=0.003). We have also established that the linear correlation between all motor skill variables and performance is high (R=0.72, p=0.006). The findings of this study show the suitability of the chosen variables in determining the potential success of young alpine skiers.